Risk Based Internal Auditing dan Implementasinya pada PT IBF - Anwar, Choirul (Journal the Winners: Economics, Business, Management, and Information System Journal, 2009)
Risks deal with uncertainties. The bigger the uncertainties faced by firms, the larger opportunity and impact of the risks in future. Whether firms succeed in managing risks it depends a lot on the effectivity of internal control. PT Indonesia Buffon Film (PT IBF) is one of many firms trying to optimalize its Internal Audit Department.The main problem in this company is managing the company to survive with accumulated losses over 90% of share capital in the period of 2007 to 2008. This research aims to describe the relationship between internal control and purpose of Internal Audit Department of PT IBF. The main focus is the management crisis happening due to weak leadership within the company. This in turn weakens internal control. Management is suggested to prioritize risks that contribute to the main risk, especially internal factors that can be controlled by management. PT IBF has deployed an implementation of the Australian/New Zealand Standard in Risk Management (AZ/NZS 4360) that helps the main purpose of the Risk Based Internal Auditing. Overall, PT IBF has done well to recognize that there are possible risks in their business operations. However, there are also gaps that must be analyzed and followed up further by management.